2020
DOI: 10.1681/asn.2019060601
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Attenuates Renal Ischemia-Reperfusion Injury by Inducing Myeloid-Derived Suppressor Cells

Abstract: BackgroundGranulocyte colony-stimulating factor (G-CSF) can increase populations of myeloid-derived suppressor cells, innate immune suppressors that play an immunoregulatory role in antitumor immunity. However, the roles of myeloid-derived suppressor cells and G-CSF in renal ischemia-reperfusion injury remain unclear.MethodsWe used mouse models of ischemia-reperfusion injury to investigate whether G-CSF can attenuate renal injury by increasing infiltration of myeloid-derived suppressor cells into kidney tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…The treatment with G-CSF increased a renal infiltration of myeloid-derived suppressor cells [48]. Nevertheless, G-CSF showed renal protective activity in a model of kidney ischemia-reperfusion [48] and diabetic nephropathy [49,50]. The data is inconsistent with our results, indicating an increase in the level of G-CFS in patients with reduced renal function, especially those with NA-CKD.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The treatment with G-CSF increased a renal infiltration of myeloid-derived suppressor cells [48]. Nevertheless, G-CSF showed renal protective activity in a model of kidney ischemia-reperfusion [48] and diabetic nephropathy [49,50]. The data is inconsistent with our results, indicating an increase in the level of G-CFS in patients with reduced renal function, especially those with NA-CKD.…”
Section: Discussioncontrasting
confidence: 86%
“…Renal ischemia-reperfusion induces G-CSF gene expression in thick ascending limb cells and increased serum concentration of G-CSF [47]. The treatment with G-CSF increased a renal infiltration of myeloid-derived suppressor cells [48]. Nevertheless, G-CSF showed renal protective activity in a model of kidney ischemia-reperfusion [48] and diabetic nephropathy [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recent study that reported the natural expansion of MDSCs following heart allograft transplantation in mice that favor graft survival prolongation [106]. In the context of renal IRI, a recent study by Yan et al [107] evaluated the role of MDSCs using an experimental model and found that after induction by granulocyte colony-stimulating factor (G-CSF), MDSC secrete arginase-1 (ARG-1), which prevents T cell proliferation and potent immune responses. In this model, while MDSC would appear as protective, other studies have reported that MDSCs are mobilized by CRP to further exacerbate renal damage in IRI [108].…”
Section: Cellular Regulation Of Danger Signalssupporting
confidence: 86%
“…M1 polarization occurs via stimulation with several pro-inflammatory signals (e.g., LPS and IFNγ, with ensuing TNFα, and IL-6 production) ( 15 23 ), as are normally elicited early after bacterial infection of the urinary tract ( 104 106 ). M2 macrophages are sensitive to a variety of Th2 cytokines, including CXCL1, G-CSF and IL-10 ( 27 , 31 33 ). The whole-kidney cytokine profiles following UPEC infection aligned with the macrophage polarization states we observed, with androgenized mice exhibiting suppressed IFNγ and unaltered TNFα, accompanied by increased CXCL1 and G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…These M1 cells further secrete proinflammatory cytokines and chemokines, exert phagocytic activity, and induce neutrophil apoptosis (25)(26)(27)(28)(29)(30). Reduction of local DAMP and PAMP quantities, along with an increase in neutrophil debris, and accumulation of T H 2 cytokines, including cytokines such as CXCL1, G-CSF, and IL-10 (27,(31)(32)(33), subsequently encourages these M1 macrophages to polarize toward alternatively activated M2 macrophages (34)(35)(36)(37)(38). M2a macrophages are activated by IL-4 and IL-13, and are considered pro-fibrotic (39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%